Vinification and aging: how much oxygen to add and when? - Rémy Ghidossi; Fabrice Meunier (IVES Technical Reviews, 2020)
In his day, Pasteur already identified the importance of oxygen to wine and his famous quotation is often repeated: “It’s oxygen that makes wine.” A great deal of scientific work has been done on the impact of oxygen on wine. This article aims to review current thinking on the quantities of oxygen that are, or should be, supplied to wine during vinification and aging.